Rock reinforcement and rock support - Aydan, Ömer (CRC Press/Balkema, 2017)
"The stability of underground and surface geotechnical structures during and after excavation is of great concern as any kind of instability may result in damage to the environment as well as time-consuming high cost repair work. The forms of instability, their mechanisms and the conditions associated with them must be understood so that correct stabilisation of the structure through rock reinforcement and/or rock support can be undertaken. This book aims to provide the fundamentals of rock reinforcement and support and to evaluate the reinforcement effects of rockbolts and rock anchor of rock engineering structures under various rock mass conditions both qualitatively and quantitatively."--Provided by publisher.
Keywords: Rock mechanics.; Engineering geology.; Geotechnical engineering.; elektronické knihy; electronic books